Respuesta :

Answer:

[tex]g(h(-8)) = 119[/tex]

Hence, option B) is true.

Step-by-step explanation:

Given

g(x) = 2x-5

h(x) = x² - 2

To determine

[tex]g(h(-8)) = ?[/tex]

In order to determine g(h(-8)), first we need to determine h(-8), so

substituting x = -8 in h(x) = x² - 2

h(x) = x² - 2

h(-8) = (-8)² - 2

h(-8) = 64 - 2

h(-8) = 62

so we can write

[tex]g(h(-8)) = g(62)[/tex]

now, to determine g(62), substitute x = 62 in g(x) = 2x-5v

g(x) = 2x-5

g(62) = 2(62) - 5

g(62) = 124 - 5

g(62) = 119

so,

[tex]g(h(-8)) = g(62)=119[/tex]

Therefore,

[tex]g(h(-8)) = 119[/tex]

Hence, option B) is true.

ACCESS MORE